Higher Clinician-Patient Communication Is Associated With Greater Satisfaction With HIV Care - Juddy Wachira PhD (SAGE Publishing, 2021)
Provider-patient communication (PPC) skills are key in promoting patient satisfaction. Our study examined the relationship between clinician PPC skills and patient satisfaction with care among virally unsuppressed adult HIV patients in Busia County, Kenya. This cross-sectional study was conducted among 360 HIV patients on first line antiretroviral regimen and having a recent viral load ≥400 copies HIV RNA/ml. We conducted logistic regression analysis. The mean age of participants was 48.2 years [standard deviation (SD): 12.05]. Overall, the mean score on clinician PPC skills was 33.3 (SD: 9.0). A high proportion (85%) of participants reported satisfaction with the HIV care services. After adjusting for covariates, the odds of being satisfied with care increased by 19% (adjusted odds ratio: 1.19, 95% CI: 1.11-1.30) for every one unit increase in the clinician PPC skills score. Promoting good PPC skills may be key to improving patient satisfaction with HIV care.